System for predicting genetic diseases and conditions using neural networks - EGGILSEN, AGUST, SVELIL (2024)
Apparatuses, methods, and computer program products for training and utilizing neural networks are disclosed. An exemplary method includes obtaining sequencing variant sample data and training a neural network using the sequencing variant sample data. The example method further includes training a neural network by altering values at one or more loci of one or more samples in the sequencing variant sample data to produce altered sequencing variant sample data, and using the altered sequencing variant sample data as an input during training of the neural network, the neural network is caused to be trained to predict values from unaltered sequencing variant sample data and one or more reference genomic maps. Another exemplary method includes obtaining subject sequencing variant sample data of a subject and generating predictors of a genome using a neural network. The method also includes determining one or more predicted conditions of the subject. 公开了用于训练和利用神经网络的装置、方法和计算机程序产品。示例性方法包括获得测序变体样品数据以及使用该测序变体样品数据训练神经网